Distribution of insect in organic guava (Psidium guajava) orchard at Lanchang, Pahang - Omar, Nurul Alia; Abdul, Nurul Huda (2022)
Insects are important for a broad selection of ecosystem services that benefits living organisms such as humans and animals. Insects community is on decline due to habitat loss, exotic species invasions, pollution, overharvesting, and land use changes. This present study analyzed the total abundance and diversity of insect that visited organic guava (Psidium guajava) orchards with increasing distance from the edge. Data were collected through sampling method using Malaise traps at different distances (5m, 10m, 20m, 40m) from the edge from July 2020 until June 2022. A total of 12,045 insects from 14 orders, 149 families and 605 morphospecies were recorded. This study shows that Diptera (46.22%) was the most dominant order according to total number of individuals, followed by Lepidoptera (20.66%), Hemiptera (13.73%), Hymenoptera (12.07%) and Coleoptera (5.53%). Others were collected less than 5%. Higher Menhinick’s index (5.560) indicated rich insect community in this orchard. However, Simpson’s evenness indicated the abundance among the morphospecies is not evenly distributed (0.002) and low Simpson’s index of diversity calculated (0.293) due to some dominant genera such as Forcimpomyia (Ceratopogonidae) that was collected extremely higher in number compared to others. Based on statistical analysis using one-way ANOVA, there is no significant difference at p=0.05 between the total number of insect morphospecies sampled for each order between distances from the edge of the orchard. This study demonstrates that guava is visited by variety of insect taxa. However, in this organic guava orchard, distance from the edge have no significant influence on their community composition.